MicroRNA-122-5p prevents proliferation and promotes apoptosis of hepatic stellate cells by suppressing the cellular-Abelsongene/histone deacetylases 2 pathway. (19th January 2022) - Wu, ZongYang; Wang, JinBo; Feng, JiYe; Ying, LiPing
Liver fibrosis is a wound-healing response and the activation of the hepatic stellate cell (HSC) is the core of hepatic fibrosis. MicroRNAs (miRNAs) participate in the development of fibrosis. It is reported that histone deacetylases (HDAC2) tyrosine phosphorylation by cellular-Abelsongene (c-Abl) induces malignant growth of cells. Here, we investigated the effect of miR-122-5p on the proliferation and apoptosis of HSCs. Normal human HSC line LX-2 and LX-2 cells stimulated by transforming growth factor (TGF)-β1 for 24 h were cultured and assigned into the blank group and the TGF-β1 group. The miR-122-5p inhibitor and its negative control were transfected into LX-2 cells and miR-122-5p mimic and its negative control were transfected into LX-2 cells stimulated by TGF-β1. The result showed that miR-122-5p expression was decreased in TGF-β1-stimulated LX-2 cells. miR-122-5p overexpression reduced the mRNA and protein levels of collagen I and α-smooth muscle actin, inhibited cell proliferation, and accelerated cell apoptosis. miR-122-5p targeted c-Abl. Meanwhile, miR-122-5p overexpression inhibited HSC activation by suppressing the c-Abl/HDAC2 pathway. In summary, miR-122-5p overexpression exerted anti-fibrosis effect and inhibited HSC activation by suppressing the c-Abl/HDAC2 pathway.